Aspects of the biology of, and fishery for, the Hottentot, Pachymetopon blochii (Val.) (Sparidae), in the Western and Southwestern Cape - Pulfrich, Andrea Christine (Department of Biological Sciences, 2016)
Data extracted from historic records have been used together with information collected during a survey of major fishing centres in the west and southwest Cape, from Port Nolloth to Struis Bay, to document the development of the handline fishery, with special reference to the fishery for hottentot Pachymetopon blochii (Val.). The fishing communities are described and social conditions are compared with those reported in earlier surveys. Changes in the fishing vessels and tackle used in the handline fishery are described and the economic status of the fishery evaluated. The distribution and availability of P. blochii are assessed in relation to the various tackle types and catch methods in different areas and the contribution by this species to the total annual linefish catch is estimated. Total fishing effort expended in the commercial linefishery is used to calculate catch-per-unit-effort indices for the hottentot fishery and the seasonal and long-term trends in these indices are evaluated in relation to past and present constraints on the marketing of this species.